A generic method of engagement to elicit regional coastal management options. (May 2016) - Dichmont, Catherine M.; Dutra, Leo X.C.; Owens, Randall; Jebreen, Eddie; Thompson, Carolyn; Deng, Roy A.; van Putten, Elizabeth I.; Pascual, Ricardo; Dambacher, Jeffrey M.; Warne, Michael St J.; Quinn, Ross H.; Thébaud, Olivier; et al.
Abstract: Stakeholder engagement is important for successful management of natural resources, both to make effective decisions and to obtain support. However, in the context of coastal management, questions remain unanswered on how to effectively link decisions made at the catchment level with objectives for marine biodiversity and fisheries productivity. Moreover, there is much uncertainty on how to best elicit community input in a rigorous manner that supports management decisions. A decision support process is described that uses the adaptive management loop as its basis to elicit management objectives, priorities and management options using two case studies in the Great Barrier Reef, Australia. The approach described is then generalised for international interest. A hierarchical engagement model of local stakeholders, regional and senior managers is used. The result is a semi-quantitative generic elicitation framework that ultimately provides a prioritised list of management options in the context of clearly articulated management objectives that has widespread application for coastal communities worldwide. The case studies show that demand for local input and regional management is high, but local influences affect the relative success of both engagement processes and uptake by managers. Differences between case study outcomes highlight the importance of discussing objectives prior to suggesting management actions, and avoiding or minimising conflicts at the early stages of the process. Strong contributors to success are a) the provision of local information to the community group, and b) the early inclusion of senior managers and influencers in the group to ensure the intellectual and time investment is not compromised at the final stages of the process. The project has uncovered a conundrum in the significant gap between the way managers perceive their management actions and outcomes, and community's perception of the effectiveness (and wisdom) of these same management actions. Highlights: Stakeholder engagement is important for successful regional management. A generic decision support process is described using two case studies. Method to elicit management objectives and options, with priorities, are provided. A generic elicitation framework for use by others is suggested.